2012
DOI: 10.1016/j.neubiorev.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Interacting brain systems modulate memory consolidation

Abstract: Emotional arousal influences the consolidation of long-term memory. This review discusses experimental approaches and relevant findings that provide the foundation for current understanding of coordinated interactions between arousal activated peripheral hormones and the brain processes that modulate memory formation. Rewarding or aversive experiences release the stress hormones epinephrine (adrenalin) and glucocorticoids from the adrenal glands into the bloodstream. The effect of these hormones on memory cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
137
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(149 citation statements)
references
References 213 publications
(250 reference statements)
9
137
0
3
Order By: Relevance
“…However, evidence also indicates that different types or kinds of learning involve separate and distinct brain regions, as, for example, the hippocampus and caudate are involved in the consolidation of spatial and cued water maze learning, respectively (Packard et al 1994). The BLA interacts with a variety of structures both cortical (e.g., anterior cingulate cortex, insular cortex) and subcortical (e.g., caudate, nucleus accumbens) during memory consolidation, potentially accounting for its diffuse involvement in consolidation across tasks and types of memory (for recent review, see McIntyre et al 2012). However, prior work was unable to directly manipulate activity in distinct efferent BLA pathways to determine whether such pathways were selectively involved in specific kinds of memory consolidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence also indicates that different types or kinds of learning involve separate and distinct brain regions, as, for example, the hippocampus and caudate are involved in the consolidation of spatial and cued water maze learning, respectively (Packard et al 1994). The BLA interacts with a variety of structures both cortical (e.g., anterior cingulate cortex, insular cortex) and subcortical (e.g., caudate, nucleus accumbens) during memory consolidation, potentially accounting for its diffuse involvement in consolidation across tasks and types of memory (for recent review, see McIntyre et al 2012). However, prior work was unable to directly manipulate activity in distinct efferent BLA pathways to determine whether such pathways were selectively involved in specific kinds of memory consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…However, work strongly indicates that the basolateral amygdala (BLA) modulates the consolidation of a wide array of memories. It has been hypothesized that the BLA plays this more general role, at least in part, through interactions with distinct regions (McGaugh 2002(McGaugh , 2004McIntyre et al 2012). BLA connections with forebrain regions such as the hippocampus and striatum that are selectively involved in the consolidation of certain kinds of memories (McDonald 1991;PitkĂ€nen et al 2000;McGaugh 2002;Malin and McGaugh 2006;Paz et al 2006;Chavez et al 2013) suggest that efferent pathways from the BLA may be selectively involved in modulating consolidation for specific kinds of information.…”
mentioning
confidence: 99%
“…Other peripherally acting agents that conduct ascending information through the vagus nerve demonstrate a similar inverted-U response [4,5,[135][136][137][138]. The precise mechanisms that underlie this response profile are not understood, but several explanations could account for the inverted-U response.…”
Section: Optimizing Vns Parametersmentioning
confidence: 99%
“…Third, cued conditioning relies on the amygdala, but in the case of a conditioning relying on context, the hippocampus would additionally be recruited [97]. Fourth, a lot of studies have shown that a stimulation of the amygdala enhances hippocampal-dependent memory and modulates the synaptic plasticity in the hippocampus (e.g., [1,2,40,69,93,100,102,104]). Fifth, learning to suppress conditioned responses requires interactions between the hippocampus and the (basolateral) amygdala.…”
Section: Interactions Between the Amygdala And The Hippocampusmentioning
confidence: 99%